The burden of alcohol on health care during COVID‐19. (24th August 2020) - Stockwell, Tim; Andreasson, Sven; Cherpitel, Cheryl; Chikritzhs, Tanya; Dangardt, Frida; Holder, Harold; Naimi, Timothy; Sherk, Adam
Abstract: Alcohol's impact on global health is substantial and of a similar order of magnitude to that from COVID‐19. Alcohol now also poses specific concerns, such as increased risk of severe lung infections, domestic violence, child abuse, depression and suicide. Its use is unlikely to aid physical distancing or other preventative behavioural measures. Globally, alcohol contributes to 20% of injury and 11.5% of non‐injury emergency room presentations. We provide some broad comparisons between alcohol‐attributable and COVID‐19‐related hospitalisations and deaths in North America using most recent data. For example, for Canada in 2017 it was recently estimated there were 105 065 alcohol‐attributable hospitalisations which represent a substantially higher rate over time than the 10 521 COVID‐19 hospitalisations reported during the first 5 months of the pandemic. Despite the current importance of protecting health‐care services, most governments have deemed alcohol sales to be as essential as food, fuel and pharmaceuticals. In many countries, alcohol is now more readily available and affordable than ever before, a situation global alcohol producers benefit from and have helped engineer. We argue that to protect frontline health‐care services and public health more generally, it is essential that modest, evidence‐based restrictions on alcohol prices, availability and marketing are introduced. In particular, we recommend increases in excise taxation coupled with minimum unit pricing to both reduce impacts on health‐care services and provide much‐needed revenues for governments at this critical time.